Factors Associated with Musculoskeletal Disorders (MSDs) in Nurses in Hospital Inpatient Areas - Rizki Yeni Wulandari; Yunina Elasari; M. Rifqi Abdillah (GLOBAL HEALTH SCIENCE GROUP, 2026)
Nurses are healthcare workers with a high physical workload, requiring them to perform various activities such as lifting, moving, and maintaining patient positions for extended periods. These activities can cause repetitive stress on the muscular and skeletal systems, potentially leading to musculoskeletal disorders (MSDs). The research objective was to determine the factors associated with Musculoskeletal Disorders (MSDs) in nurses in the inpatient ward of the Regional General Hospital. The quantitative research method used a cross-sectional design, with data collection using questionnaires and observation methods. This study used the Rapid Entry Body Assessment (REBA) instrument with a validity of 0.61 and a reliability of 0.625. The Nordic Body Map (NBM) questionnaire has a validity test result of 0.543-0.768 with a reliability test of 0.720. The study sample consisted of all nurses working in the inpatient ward of the Regional General Hospital in 2025, totaling 164 respondents. Total sampling was the method of sample that was employed. Bivariate data analysis used the Spearman test. The results of the analysis showed that there was a significant relationship between ergonomic position and the risk of musculoskeletal disorders, with a p value = 0.001 and a correlation coefficient (r) = 0.348 indicating a positive relationship with moderate strength. Meanwhile, age (p = 0.064), length of service (p = 0.137), length of service (p = 0.166), and workload (p = 0.598) did not show a significant relationship with the incidence of musculoskeletal disorders in nurses in the inpatient ward. This study showed a significant association between ergonomic positioning and the risk of musculoskeletal disorders in nurses in inpatient wards. However, age, length of service, length of service, and workload were not significantly associated with the development of musculoskeletal disorders.